2021
DOI: 10.1021/acs.energyfuels.1c03011
|View full text |Cite
|
Sign up to set email alerts
|

Mn0.26V2O5·nH2O Nanoribbons with Fast Ion Diffusion Channels and High Electrical Conductivity for Intercalation Pseudocapacitive Zn2+ Storage

Abstract: Zn 2+ intercalation pseudocapacitance is a desirable reaction mechanism to achieve high-energy and high-power-density aqueous zinc-ion batteries (AZIBs). However, engineering an intercalation pseudocapacitive cathode for AZIBs remains challenging owing to the sluggish Zn 2+ diffusion kinetics and low electrical conductivity of cathode materials. Here, a novel Mn 0.26 V 2 O 5 •nH 2 O nanoribbon cathode synthesized by a facile ionpreintercalated/-doped strategy is reported for intercalation pseudocapacitive Zn 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Typical peaks located at 518, 766, and 1002 cm À1 assign to the interaction between V and O, the peaks at 933 cm À1 indicate the formation of Mn O bonds, while the visible peaks at 1620 cm À1 attribute to the O H vibration in the H 2 O molecules (Figure 2C). 37,38 These results confirm the formation of Mn 2+ -ions and H 2 O molecule co-inserted vanadium oxides. Notably, apart from the characteristic bands of MnVOH, there were some discriminative peaks in concert with the interaction between C, S, and O (e.g., the peaks at 1506 and 1407 cm À1 of C C and C C bonds, at 1247, 1156, and 1070 cm À1 of C O C bonds, as well as the peaks at 1116 cm À1 of C S bonds), suggesting the formation of PEDOT in MnVOH@PEDOT.…”
Section: Synthesis and Characterizationsupporting
confidence: 63%
“…Typical peaks located at 518, 766, and 1002 cm À1 assign to the interaction between V and O, the peaks at 933 cm À1 indicate the formation of Mn O bonds, while the visible peaks at 1620 cm À1 attribute to the O H vibration in the H 2 O molecules (Figure 2C). 37,38 These results confirm the formation of Mn 2+ -ions and H 2 O molecule co-inserted vanadium oxides. Notably, apart from the characteristic bands of MnVOH, there were some discriminative peaks in concert with the interaction between C, S, and O (e.g., the peaks at 1506 and 1407 cm À1 of C C and C C bonds, at 1247, 1156, and 1070 cm À1 of C O C bonds, as well as the peaks at 1116 cm À1 of C S bonds), suggesting the formation of PEDOT in MnVOH@PEDOT.…”
Section: Synthesis and Characterizationsupporting
confidence: 63%
“…Figure b gives the b -values of peaks 1 and 2 (0.71 and 0.94, respectively), showing that MoO 2 /C-rGO is controlled by a hybrid mechanism of diffusion and capacitance. The k 1 – k 2 analysis was used to separate the capacitive and diffusion-controlled charges at a scan rate of 1.5 mV s –1 , the capacitive charge reaches a very high ratio of 85.3% (Figure c). We also calculated the capacitive charge at other scan rates (Figure d) and found that the capacitance dominates the electrochemical reaction.…”
Section: Resultsmentioning
confidence: 99%
“…S12 †), which means that some Zn 2+ ions are adsorbed on the surface. 54,55 In other words, some of the Zn 2+ ions are embedded in the interlayer, and some are adsorbed on the surface of the material.…”
Section: Mechanism Of Zn 2+ Storagementioning
confidence: 99%